Pembaca Meter Jarak Jauh (Long Distance Meter Reader) - Abdullah, Siti Noor Kartini (Universiti Sains Malaysia, 2006)
This final year project is titled Long Distance Meter Reader. Meter readers nowadays still require man power. Thus this Long Distance Meter Reader is a system created to read data through a computer without using any man power. It reads the data directly through a cable which is connected to the control port for TNB and sent to every consumer’s home. All the sending and receiving process is done by two controller or two segments where one segment is to send data (from the consumer’s house code) and the other one to receive the code data. The accepted code data are then compared to ensure either the code entered is the same with the specified code or not. The meter reader’s output will be displayed on the computer screen. Microcontroller 8051 is used to control the whole long-distance meter reader project where the sending and receiving code process is done by UART which in built inside the microcontroller 8051.